Meningkatkan Fleksibilitas Kerj a : Suatu Upaya Menangani Konflik Antar Kelompok di Universitas Kristen Duta Wacana - Mega Wati (Jurnal Riset Manajemen dan Bisnis, 2007)
Conflicts are inevitable in a work context. Therefore, understanding the causes of conflicts and how to solve them becomes significance for the effictiveness of an organization. Based on a case study at Duta Wacana Christian University (DWCU), this paper focuses on how to solve conflictsby increasing the work flexibility. It will start with a closer look at the theory of intergroup conJlicts and the causes, as well as the interttention technique. Then, moving to the context of an organization, it will describe the sources of conflicts and the common conflict managernent styles in DWCU. Finally, this paper will recommend the most appropriate strategtt in managing intergroup conflicts in DWCU based on the modification of the interttention technique and the embedded concepts of Brown and Harvqt's boundaryles sness and fl exibility and Zand's collateral organization.Keywords : Inter group conflict management, Organization development.